2013
DOI: 10.1038/nn.3350
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of LRRK2 with chaperone-mediated autophagy

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) are the most common cause of familial Parkinson’s disease (PD). In this work, we demonstrate that LRRK2 can be degraded in lysosomes by chaperone-mediated autophagy (CMA), whereas the most common pathogenic mutant form of LRRK2, G2019S, is poorly degraded by this pathway. In contrast to typical CMA substrates, lysosomal binding of both wild-type and several pathogenic mutant LRRK2 proteins is enhanced in the presence of other CMA substrates, which interferes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
494
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 527 publications
(518 citation statements)
references
References 55 publications
21
494
1
2
Order By: Relevance
“…Reduced tau‐P301L uptake is not caused by a problem in translocation across the lysosomal membrane, but rather by reduced targeting/binding to lysosomes, as we did not detect tau accumulation at the lysosomal membrane. This is in clear contrast to other pathogenic proteins such as mutant α‐synuclein or mutant LRRK2 that bind to lysosomes but fail to translocate through CMA (Cuervo et al ., 2004; Orenstein et al ., 2013). In the case of tau‐A152T, the dynamics of internalization/degradation through CMA were comparable to WT tau (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced tau‐P301L uptake is not caused by a problem in translocation across the lysosomal membrane, but rather by reduced targeting/binding to lysosomes, as we did not detect tau accumulation at the lysosomal membrane. This is in clear contrast to other pathogenic proteins such as mutant α‐synuclein or mutant LRRK2 that bind to lysosomes but fail to translocate through CMA (Cuervo et al ., 2004; Orenstein et al ., 2013). In the case of tau‐A152T, the dynamics of internalization/degradation through CMA were comparable to WT tau (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6a–c). This finding rules out that diminished translocation could be due to oligomerization or aggregation of this mutant at the surface of lysosomes, which was previously described to be the case for pathogenic proteins such as α‐synuclein or LRRK2 (Cuervo et al ., 2004; Orenstein et al ., 2013). Although the tendency of hTau40 ΔK280 to aggregate could be the determinant of its poor clearance by CMA, we propose a direct effect of this mutation on tau's ability to undergo degradation through CMA, as inefficient CMA of hTau40 ΔK280 seems, in part, independent of aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Such mishandling of aberrant proteins alters proteostasis and often leads to the precipitation of protein aggregates that contribute to neuronal demise [49]. The involvement of CMA in neurodegeneration is two-fold, as it contributes to the elimination of pathogenic proteins, but also often, becomes victim of the toxic effect of these aberrant proteins [50][51][52][53]. This dual role of CMA in neurodegenerative disorders makes it necessary to analyze the status of this autophagy pathway in disease in order to determine whether interventions aimed at enhancing CMA activity could be of potential value or not, depending on the degree of compromise of this pathway and the reversibility of the CMA blockage.…”
Section: Reduced Cma and Neurodegenerationmentioning
confidence: 99%
“…A recent investigation of leucine-rich repeat kinase 2 (LRRK2), mutation of which is linked to PD, showed that it is a CMA substrate [56] . LRRK2 G2019S, the most common mutant form, is poorly degraded by this pathway.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…This decrease is in part due to the accelerated removal of oxidized MEF2D by CMA. Consistently, the levels of oxidized MEF2D are much higher in the postmortem PD brain than in controls, consistent with the notion that reduced CMA in PD leads to the accumulation of damaged MEF2D, disrupting its homeostasis and function.A recent investigation of leucine-rich repeat kinase 2 (LRRK2), mutation of which is linked to PD, showed that it is a CMA substrate [56] . LRRK2 G2019S, the most common mutant form, is poorly degraded by this pathway.…”
mentioning
confidence: 99%